Cover Feature: Liquid‐Phase Cyclohexene Oxidation with O2 over Spray‐Flame‐Synthesized La1−xSrxCoO3 Perovskite Nanoparticles (Chem. Eur. J. 68/2021). Issue 68 (28th October 2021) - Büker, Julia; Alkan, Baris; Chabbra, Sonia; Kochetov, Nikolai; Falk, Tobias; Schnegg, Alexander; Schulz, Christof; Wiggers, Hartmut; Muhler, Martin; Peng, Baoxiang
Abstract : The liquid‐phase oxidation of cyclohexene was studied over a series of Sr‐substituted La1− x Sr x CoO3 catalysts of perovskite structure under mild reaction conditions with O2 as oxidant in an autoclave. The substitution of Sr into the perovskite structure led to the formation of catalytically active oxygen species. In‐situ ATR IR measurements provided a comprehensive insight into the reaction mechanism under oxidation reaction conditions. More information can be found in the Full Paper by H. Wiggers, B. Peng et al. (DOI: 10.1002/chem.202103381 ).